Integrative analysis of physiology, biochemistry and transcriptome reveals the mechanism of leaf size formation in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Wang, Lixia; Zhang, Shu; Zhang, Ye; Li, Jingjuan; Zhang, Yihui; Zhou, Dandan; Li, Cheng; He, Lilong; Li, Huayin; Wang, Fengde; Gao, Jianwei (Frontiers in Plant Science, 2023)
The leaf, the main product organ, is an essential factor in determining the growth, yield and quality of Chinese cabbage. To explore the regulatory mechanism of leaf size development of Chinese cabbage, we investigated the leaf size difference between two high-generation inbred lines of Chinese cabbage, Y2 (large leaf) and Y7 (small leaf). Furtherly, the transcriptome and cis-acting elements analyses were conducted. Our results showed that the leaf number and size of Y2 were significantly larger than Y7. In addition, Y2 exhibited a higher growth rate than Y7 during the whole growth stage. Scanning electron microscope showed that cell numbers caused the difference in leaf size. The measurement of phytohormone content confirmed that GA1 and GA3 mainly play essential roles in the early stage of leaf growth, and IPA and ABA were in the whole leaf growth period in regulating the cell proliferation difference between Y2 and Y7 Chinese cabbage. Transcriptome analysis revealed that cyclins BraA09g010980.3C (CYCB) and BraA10g027420.3C (CYCD) were mainly responsible for the leaf size difference between Y2 and Y7. Further, we revealed that the transcription factors BraA09gMYB47 and BraA06gMYB88 played critical roles in the difference in leaf size between Y2 and Y7 through the regulation of cell proliferation. This observation offers essential insights into understanding the leaf size development regulation mechanism and provides a promising breeding strategy to improve Chinese cabbage yield.